Biocompatibility and inflammatory response of silver tungstate, silver molybdate, and silver vanadate microcrystals - Pimentel, Bruna Natália Alves da Silva; De Annunzio, Sarah Raquel; Assis, Marcelo; Barbugli, Paula Aboud; Longo, Elson; Vergani, Carlos Eduardo (Frontiers in Bioengineering and Biotechnology, 2023)
Silver tungstate (α-Ag2WO4), silver molybdate (β-Ag2MoO4), and silver vanadate (α-AgVO3) microcrystals have shown interesting antimicrobial properties. However, their biocompatibility is not yet fully understood. Cytotoxicity and the inflammatory response of silver-containing microcrystals were analyzed in THP-1 and THP-1 differentiated as macrophage-like cells, with the alamarBlue™ assay, flow cytometry, confocal microscopy, and ELISA. The present investigation also evaluated redox signaling and the production of cytokines (TNFα, IL-1β, IL-6, and IL-8) and matrix metalloproteinases (MMP-8 and -9). The results showed that α-AgVO3 (3.9 µg/mL) did not affect cell viability (p > 0.05). α-Ag2WO4 (7.81 µg/mL), β-Ag2MoO4 (15.62 µg/mL), and α-AgVO3 (15.62 µg/mL) slightly decreased cell viability (p < 0.003). All silver-containing microcrystals induced the production of O2 -and this effect was mitigated by Reactive Oxygen Species (ROS) scavenger and Nacetylcysteine (NAC). TNFα, IL-6 and IL-1β were not detected in THP-1 cells, while their production was either lower (p < 0.0321) or similar to the control group (p > 0.1048) for macrophage-like cells.The production of IL-8 by both cellular phenotypes was similar to the control group (p > 0.3570). The release of MMP-8 was not detected in any condition in THP-1 cells. Although MMP-9 was released by THP-1 cells exposed to α-AgVO3 (3.9 µg/mL), no significant difference was found with control (p = 0.7). Regarding macrophage-like cells, the release of MMP-8 and -9 decreased in the presence of all This is a provisional file, not the final typeset article microcrystals (p < 0.010). Overall, the present work shows a promising biocompatibility profile of, α-Ag2WO4, β-Ag2MoO4, and α-AgVO3 microcrystals.